Devising and demonstrating an extreme weather risk indicator for use in transportation systems - Leviakangas, Pekka; Molarius, R.; Könönen, V.; Zulkarnain, Z.; Hietajärvi, A. (NATL ACAD Sciences, 2013)
This paper describes a novel risk indicator for extreme weather risks for use in transportation systems. The risk indicator is applied to the European transportation system indicating and ranking the risks for the 27 member states of the European Union (EU-27). The paper starts with definitions of hazards, vulnerability, and risk, based on relevant literature, and then operationalizes the risk, hazard, and vulnerability with the help of EU-27 data. Finally, the paper discusses the extreme weather risk indicator (EWRI) and evaluates its applicability and limitations. The risk indicator is a relative indicator: it should be viewed and treated as a ranking system. The devised indicator is able to assist decision makers at national and state as well as international and federal levels in the prioritization of extreme weather risks within their jurisdiction. The overall approach of EWRI is based on mainstream risk and vulnerability assessment research, following for the most part the existing conceptual models. The novelty of EWRI lies in its application area (transportation) and wide use of both empirical and statistical data. EWRI was used to assess the hazards, vulnerabilities, and risks of extreme weather for the EU-27, but nothing hinders its application, either in this form or a modified form, in other contexts.